Basic strength properties of oncosperma tigillarium at small clear - Mohd Faiz Jafni, bin Ahmad Mustafa (Universiti Malaysia Sarawak (UNIMAS), 2014)
In the modem world today, concrete jungles are spreading like wildfire all over the world pushing natural forests out of the way. Concrete becomes an ever demanded construction material; however the price of concrete is not cheap. Therefore, timber, a renewable and eco-friendly construction material is sought out as an alternative in the construction industry. Like any other materials, timber has its own setbacks in terms of biological degradation, chemical resistance, dimensional stability, thermal resistance, weathering and decay. However, if treated properly, timber can become a fierce adversary to concrete. Moreover, timber has a very high aesthetic value compared to other construction materials. Hardwood is the type of timber often chosen as structural material as it has higher strength, but requires a very long time to mature; about 100 years. Thus, a species of fast-growing timber of name Oncosperma Tigillarium or better known for its common name, Nibong palm is chosen to be experimented on to determine its basic physical properties and mechanical properties in the search for an alternative to hardwood timber. Therefore, a series of tests were conducted on air dry specimens of Oncosperma Tigillarium to study the strength properties such as bending properties, compressive strength parallel to grain, hardness and impact resistance between samples from different culms. Tests are carried out in accordance to British Standard 373: 1957 Method for testing small clear specimens of timber. Specimens were obtained within the vicinity of the Universiti Malaysia Sarawak (UNIMAS) campus. The laboratory tests were conducted at the Sarawak Forestry Corporation (SFC). Based on the data analysis, Oncosperma Tigillarium shows strength properties which are comparable to other medium hardwood or even hardwood even though is it classified to be a non-worthy timber .